An Evaluation of the Short‐Term Progress of Restoration Combining Ecological Assessment and Public Perception. Issue 1 (7th March 2012) - Petursdottir, Thorunn; Aradottir, Asa L.; Benediktsson, Karl
<x xml:space="preserve">Abstract</x> Ecological restoration centers on the reestablishment of ecological processes and the integrity of degraded ecosystems, but its success also depends on public acceptance and support. In this study, we evaluated the short‐term ecological effects of different restoration treatments in Iceland. Furthermore, we tested the public perception of aesthetic and recreational values of these revegetated areas. Predefined soil and vegetation indicators were measured, and a survey, based on a questionnaire and photographs of the different areas, was used for gauging public perception. Our results indicate that different restoration treatments triggered different succession trajectories. The vegetation composition of areas seeded with grasses seemed to be on a trajectory toward relatively undisturbed reference ecosystems, whereas areas seeded with nonnative lupine seemed to be developing a novel ecosystem. Results of the survey demonstrated that people valued the appearance of revegetated areas higher than that of the eroded control areas, with the exception of areas seeded with lupine. The visual perception of each restoration treatment corresponded well with the ecological factors and revealed both a social and an ecological rationale against the use of lupine in land restoration. The results indicate that the design of restoration projects should be based on both an analysis of sociocultural priorities and an understanding of possible trajectories of ecosystem development associated with the available restoration methods to avoid results that are neither socially acceptable nor ecologically feasible.